Entrepreneurial Orientation in the Business Profit Development Center of SMEs in Java: The Critical Role of Islamic Values - Riyoko, Sisno; Mufid, Fathul (IQTISHADIA, 2023)
Small and medium enterprises (SMEs) are urged to enhance their business operations in the rapidly evolving technological landscape. The emphasis on entrepreneurial orientation has played a crucial role in both economic and societal development. Islamic values, which are rooted in fundamental religious principles, have significant potential to shape entrepreneurial behaviors. This research aims to provide a framework that enhances the performance of SMEs. The results of this research emphasize the significant role of Islamic values in amplifying entrepreneurial orientation. This research reveals that adopting Islamic principles has the potential to significantly improve the business performance of SMEs in Central Java. In addition, SMEs benefit from a significant boost in their performance by embracing Islamic values, such as proactiveness, a commitment to learning, and the willingness to take risks.